Healthy Life Awareness of Older Adults During The Covid 19 Pandemic - Tuğçe KAPLAN UYAN; Sibel ÇAYNAK; İlkay KESER (Yaşlı Sorunları Araştırma Derneği, 2023)
Elderly individuals are the individuals most affected by the pandemic and have a high mortality rate. It is important to examine the healthy living behaviors of elderly individuals, their awareness on this issue and their relationship with cognitive, mental and behavioral variables during the pandemic process. In the study, it was aimed to determine the level of awareness of healthy life in elderly individuals during the COVID-19 pandemic process and to examine its relationship with cognitive, mental and behavioral variables during the pandemic process. The sample of the study consisted of 204 elderly individuals. The data of the research were collected between November 2021 and November 2022 by face-to-face interview method. The data were obtained by using the "Descriptive Information Questionnaire" and "Health Life Awareness Scale". Descriptive statistics were used in the analysis of the data, the independent t test was used for the difference between two independent groups in the comparison of normally distributed data, and one-way analysis of variance was used in the comparison of more than two independent groups. 57,8% of the participants perceived their health as moderate, 62,3% of them stated that there was a change in their health status during the COVID-19 pandemic, and 51,0% stated this change as a deterioration in their health. It was determined that 82,4% of the elderly individuals made behavioral changes in their lifestyle during the COVID-19 pandemic, and the most changes were related to personal care (52,0%). The mean score of the participants on the Healthy Life Awareness Scale was 50,70±9,91, and it was found that there was a significant difference (p<0,05) between the awareness scale and its sub-dimensions, being married, being a university graduate, living with a spouse, and being in good health (p<0,05). It has been determined that this awareness is associated with being married, being educated, not living alone, and being in good health. Providing training on healthy life awareness for individuals living alone, with low level of education, who are determined to have low awareness of healthy life, and in the care and treatment of elderly individuals. It is recommended that health professionals who play a role in this study plan their interventions by knowing these variables.